The perineal gland of brown lemmings, Lemmus trimucronatus - Stewart, R. E. A.; Brooks, R. J. (Canadian Journal of Zoology, 1976)
In adult male brown lemmings, Lemmus trimucronatus, a specialized pad of sebaceous glands forms the perineal gland, consisting primarily of two longitudinal ridges lateral and parallel to the midventral line of the scrotum. The ridges extend from the posterior margin of the penis sheath to the anterior edge of the rectum, and correspond externally with a pair of longitudinal furrows. Externally, the gland is characterized by brown pigmentation and coarse, transparent hairs. Histologically it is comparable to, though larger than, the rump gland of the same species. Development of the perineal gland is correlated with attainment of sexual maturity.On the basis of other studies analogous skin glands in other rodents, a scent-producing function is hypothesized for the perineal gland.